Avaliação comparativa do padrão vesical de pacientes com bexiga neurogênica em mielomeningocele operados in utero versus no período pós natal - Parizi, João Luiz Gomes [UNIFESP] (2018)
Introduction: Myelomeningocele is defined as a malformation of the central nervous system caused by the failure of the neural tube closure during the embryonic period. It was defined through observational studies that the neurological deficit results from two factors: the initial failure of neural tube formation and the continuous injury of exposed neural tissue in the intrauterine environment. Correction during the fetal period has presented positive results regarding the motor and neurological function. However, it is still necessary to improve the knowledge about the bladder pattern of patients with MMC and neurogenic bladder, as well as to investigate their relationship with the period of correction of the neurological defect. Objective: To evaluate the possible urologic benefits of patients undergoing in utero MMC correction. Methods: Three groups of patients were analyzed in a serial and retrospective way: Group 1 (patients submitted to MMC correction during the fetal period) formed by 88 patients; Group 2 (patients undergoing MMC correction after birth) was formed by 86 patients, and Group 3 formed by 38 patients of the previous group who started the follow-up before 12 months of life. The collected data for analysis and comparison of these groups were based on patients overall characteristics, urological and urodynamic tests, evolution of the bladder pattern and bladder response to treatment. Results: Group 1 presented the same number of female and male patients; the female sex prevailed in groups 2 and 3. The presence of UTI was statistically higher in patients operated in the postnatal period, corresponding to 45% of patients, whereas in Group 1 this feature corresponds only to 20% of patients. The presence of hydronephrosis occurred in 20.7% of Group 1, 22.6% of Group 2 and 28.9% of Group 3, without statistical significance when compared. The presence of VUR was verified in all the analyzed groups, with an occurrence of 15% in all groups. The urodynamic data showed a statistically higher prevalence of bladder hyperactivity in Group 1 (in utero) in comparison to the other groups, although no statistical difference was observed between groups regarding other urodynamic parameters (presence of urinary loss, bladder capacity and bladder compliance). The high-risk bladder pattern in the initial evaluation occurred in 56%, 50% and 46% of groups 1, 2 and 3, respectively. There was a tendency to decrease the percentages of the high risk bladder pattern and increase the percentages of the standard considered normal by assessing the clinical treatment response applied over time, in all groups. Patients with incontinent and hypoconstricting bladder tend to maintain the same bladder pattern over time. Conclusion: This study contribute to the improvement of the knowledge regarding the correction of the neural tube defect (myelomeningocele) in utero, showing that patients operated during the fetal period do not significantly improve their urological parameters when compared to patients operated in the postnatal period.